Targeted Epidural Blood Patch Treatment for Refractory Spontaneous Intracranial Hypotension in China - He, Fei-Fang; Li, Li; Liu, Min-Jun; Zhong, Tai-Di; Zhang, Qiao-Wei; Fang, Xiang-Ming (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective An epidural blood patch (EBP) is the mainstay of treatment for refractory spontaneous intracranial hypotension (SIH). We evaluated the treatment efficacy of targeted EBP in refractory SIH.Methods All patients underwent brain magnetic resonance imaging (MRI) with contrast and heavily T2-weighted spine MRI. Whole spine computed tomography (CT) myelography with non-ionic contrast was performed in 46 patients, and whole spine MR myelography with intrathecal gadolinium was performed in 119 patients. Targeted EBPs were placed in the prone position one or two vertebral levels below the cerebrospinal fluid (CSF) leaks. Repeat EBPs were offered at 1-week intervals to patients with persistent symptoms, continued CSF leakage, or with multiple leakage sites.Results Brain MRIs showed pachymeningeal enhancement in 127 patients and subdural hematomas in 32 patients. One hundred fifty-two patients had CSF leakages on heavily T2-weighted spine MRIs. CSF leaks were also detected on CT and MR myelography in 43 and 111 patients, respectively. Good recovery was achieved in all patients after targeted EBP. No serious complications occurred in patients treated with targeted EBP during the 1 to 7 years of follow-up.Conclusions Targeted and repeat EBPs are rational choices for treatment of refractory SIH caused by CSF leakage.
Keywords: SIH; CSF leakage; targeted EBP; treatment